Digital innovations and institutional barriers in agricultural input subsidy programmes in sub-Saharan Africa: Evidence from Nigeria - Ayobami Adetoyinbo; Saurabh Gupta; Victor Okoruwa (Development Policy Review, 2026)
Motivation: Agricultural input subsidy programmes are crucial for improving agricultural productivity in sub-Saharan Africa (SSA). However, there is little empirical evidence on how second-generation input subsidy programmes (SISPs) based on information and communication technology (ICT) are implemented and the institutional challenges that undermine their effectiveness. Purpose: ~This article assesses the implementation of ICT-based SISPs and their~challenges in SSA using the Nigerian e-wallet input subsidy programme as a case study. We draw on a conceptual framework that integrates the national innovation system (NIS), contingency theory, and new institutional economics. Approach and methods: We analysed expert interviews and participatory qualitative data from Process Net-Maps and focus group discussions (FGDs) using content and Process Net-Map analyses. Findings: The results show that over 20 public, private and community actors were involved in implementing the e-wallet SISP across five stages. The programme increased private-sector participation, reduced corruption, improved recipient targeting, and speeded up input delivery compared to first-generation input programmes. However, weak institutional arrangements (such as poor funding, restricted institutional collaborations, and stakeholder capability gaps) undermined the innovation aspect of the e-wallet SISP. The programme also faced five main challenges: policy inconsistency, poor information flow and weak reporting, moral hazards such as “round-tripping,” input leakage and diversion, and elite capture. The study concludes that institutional constraints, rigid organizational structures, and a narrow focus on solving first-generation programme challenges limited the ability of actors to adapt to new and evolving challenges. Policy implications: Effective SISPs and input policies require supportive institutional environments that allow actors from all sectors to function effectively. Programmes should thus be designed and managed with flexible and organic structures that foster collaboration among private, public, and community stakeholders. Continuous, stage-specific evaluations and smart governance tools, such as real-time mobile data collection and buy-back initiatives, can strengthen monitoring, input tracking, accountability, and input use incentives.
Keywords: 300; Africa; agricultural inputs; e-wallet growth enhancement support scheme (GESS); input subsidy programme; institutional challenges; Nigeria; Process Net-Maps